Relative Sit-to-Stand Power Versus Conventional Sit-to-Stand Time in the Clinical Assessment of Older Adults at Risk of Falls - Elisabet Huertas-Hoyas; Agustín Curiel-Regueros; Rafael García-Molina; Sara García-De-Villa; Eva Rincón-Herrera; Cristina Alonso-Bouzón; Luisa Ruiz-Ruiz; Antonio R. Jiménez-Ruiz; Marta Neira-Álvarez (Healthcare, 2026)
Background/Objectives: Conventional time-based sit-to-stand measures may not fully reflect lower-limb neuromuscular capacity. This study examined whether relative sit-to-stand (STS) power provides explanatory capacity compared with STS time in the functional assessment of older adults at risk of falls. Methods: A secondary cross-sectional analysis was conducted using data from the publicly available GAIT2CARE database. Participants had a documented history of falls, fear of falling, or stability problems. Absolute, relative, and allometrically scaled STS power were estimated from the five-repetition sit-to-stand test using validated equations. Associations between relative STS power, the Fried phenotype score, and conventional functional measures were examined using Spearman correlations, multiple linear regression, and ordinal logistic regression. Results: A total of 127 participants were included, of whom 111 completed the sit-to-stand test and had estimable STS power. Relative STS power was associated with lower Fried scores (ρ = −0.585), faster gait speed (ρ = 0.536), and better Timed Up and Go performance (ρ = −0.533; all p < 0.001). After adjustment for age and Timed Up and Go performance, relative STS power remained associated with lower Fried categories (B = −0.635; β = −0.450; p < 0.001). The model including relative STS power explained 39.6% of the variance in Fried score, compared with 33.1% for the corresponding model including STS time. Ordinal logistic regression confirmed the association between higher relative STS power and lower Fried categories (estimate = −1.247; p < 0.001). Conclusions: Relative STS power provides complementary information on lower-limb neuromuscular performance and shows greater explanatory capacity for Fried score than STS time when considered alongside age and Timed Up and Go performance. It may therefore complement, rather than replace, established functional measures in older adults at risk of falls.